PRAKTIK KOMUNIKASI POLITIK MAHASISWA GEN Z DALAM MERESPON ISU NASIONAL: ANALISIS PERILAKU, IDENTITAS DIGITAL, DAN POLA PARTISIPASI - Wahyono, Herry Setianto (Ilmu Komunikasi, FISIP Universitas Pasundan, 2026)
The rapid development of digital technology has fundamentally transformed political communication, especially among Generation Z (Gen Z). As digital natives, Gen Z exhibits unique behaviors in accessing, generating, and disseminating political information via social media. According to a 2024 We Are Social survey, 90.4% of Indonesian internet users aged 18-24 are active on social media, underscoring their critical role in shaping public opinion. The digital sphere has thus become the primary space for Gen Z students to express political views— through online discussions, digital campaigns, and internet-based social movements. This study adopts a qualitative approach within a constructivist paradigm, which is suitable for exploring the meanings, experiences, and political communication practices of Gen Z students in a dynamic social-digital environment. The constructivist paradigm posits that reality is multifaceted and shaped through social interaction. Findings reveal that Gen Z students heavily rely on social media platforms—primarily TikTok, Instagram, and X (Twitter)—as their main sources of political information, replacing traditional media. Informants noted that creative content formats such as short videos, infographics, and educational threads facilitated their understanding of political issues. This research confirms that Gen Z’s political communication practices are embedded within a dynamic digital ecosystem. The study concludes with three key insights into Gen Z students: their distinctive political communication behaviors, the formation of digital identities, and evolving patterns of political participation in response to national issues.